2014
DOI: 10.5424/sjar/2014122-5466
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of inorganic and organic mulching for soil salinity and sodicity control in a grapevine orchard drip-irrigated with moderately saline waters

Abstract: Soil mulching is a sensible strategy to reduce evaporation, accelerate crop development, reduce erosion and assist in weed control, but its efficiency for soil salinity control is not as well documented. The benefits of inorganic (plastic) and organic (grapevine pruning residues) mulching for soil salinity and sodicity control were quantified in a grapevine orchard (cultivars ‘Autumn’ Royal and ‘Crimson’) drip-irrigated with moderately saline waters. Soil samples were taken at the beginning and end of the 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
3
18
1
Order By: Relevance
“…This indicated that with the application of green manure and combination of gypsum + green manure help in reducing soil salinity and resulted in increasing crop yield. These results are in correlation with Aragues et al (2014) who reported that the application of organic straw mulch on soil surface reduces evaporation that resulted in reducing soil sodicity in the root zone. The same results reported by Pawar et al (2018) who stated that Ece of soil decreased with an increase in organic matter in soil.…”
Section: Electrical Conductivity (Ece)supporting
confidence: 90%
“…This indicated that with the application of green manure and combination of gypsum + green manure help in reducing soil salinity and resulted in increasing crop yield. These results are in correlation with Aragues et al (2014) who reported that the application of organic straw mulch on soil surface reduces evaporation that resulted in reducing soil sodicity in the root zone. The same results reported by Pawar et al (2018) who stated that Ece of soil decreased with an increase in organic matter in soil.…”
Section: Electrical Conductivity (Ece)supporting
confidence: 90%
“…These results indicate that crop straw drainage may produce a relatively higher soil desalination rate with less irrigation water as compared to the traditional plastic drainage pipes. This may attribute to the reason of greater water penetration through the full range of the crop stalks, while the plastic pipes allowed only partial infiltration [47]. In addition, decreasing soil salinity was observed in MSD as the soil depth increased from 0 to 80 cm.…”
Section: Variations Of Soil Salinitymentioning
confidence: 94%
“…Soil saturation extract electrical conductivity (ECe) values increased in all treatments of both grapevines along the irrigation seasons, but the increases were much lower in the mulched than in the bare soils due to reduced evaporation losses and concomitant decreases in salt evapoconcentration. A previous study concluded that the plastic mulch and, particularly, the organic mulch were more efficient than the bare soil for soil salinity and sodicity control [1]. In the same direction, Yang et al [2] reported that the surface mulch with different materials has a significant effect on reducing evaporation and decreasing soil salinity level in addition to its effect on wheat production.…”
Section: Introductionmentioning
confidence: 97%